The driving forces behind the home bias phenomenon: Evidence from Israel. Issue 4 (2nd October 2019) - Riff, Sivan; Yagil, Joseph
ABSTRACT: The home bias phenomenon is a widely investigated puzzle that is still not completely resolved. Home bias is the tendency of investors to invest excessively in domestic assets, in contradiction to the traditional optimal portfolio theories. This research attempts to unveil some of the underlying drivers behind this phenomenon. We examine the relationship between home bias and the level of risk in the portfolio, the percentage of the portfolio invested in ETFs (exchange traded funds), and the investor type (institutional vs. individual). To do so, we use monthly data from the Israeli market from January 2007 to March 2018. This study is the first to investigate the relationship between home bias and the use of ETFs as a global diversification tool. ETFs have become one of the most widespread passive investment instruments for both individual and institutional investors. Our findings show that institutional investors experience less home bias compared to individual investors. Second, an increase in the level of risk in the portfolio causes an increase in home bias. Finally, the use of ETFs has a negative relationship with home bias.